Keanekaragaman Tumbuhan Paku Epifit Di KawasanHutan Pinus Kragilan Kabupaten Magelang ProvinsiJawa Tengah - Mahendrati, Nelly, Efri Roziaty, S.Si., M.Si (2017)
Kragilan Pine Forest Magelang Regency Central Java is a forest area which is dominated by Pinus (Pinus mercusii). The other plant species exist in this area are Gaharu trees (Aquilaria malacensis) and several other plant species including fern plants. The existence of these ferns is still less attention than other plant groups and is often neglected, so the Pine Forest of Kragilan has no data on fern plants existance in the area. The aim of this research is to know the diversity of nail plant species in Kragilan Pine Forest area of Magelang Regency, Central Java. Data were collected from April 3, 2017 to April 30, 2017 using a plot method size (10m x 10m), as many as 12 plots with a distance of 30 meters. Based on the results of the study, there are 9 species of fern plants, consist of Diplazium procumbens, Belvisia spicata, Davallia pulmonalis, Davallia denticulate, Davallia solida, Dynaria quercifolia, Nephrolepis exaltata, Nephrolepis sp and selaginella ornata. The index of Deversity (H') is 0,755 . This index indicating that low Epiphytic Fern in Kragilan Pine Forest. The Highest Diversity Index is the type of Davallia solida 0.158 <1 (low) and the lowest Diversity Index is Nepholepis exaltata with a diversity index of 0.013 <1 (low).